P33 What matters to people with copd? outputs from working together for change. (15th November 2017) - Early, F; Lettis, M; Fuld, JP
Abstract : Introduction and Objectives: There is little qualitative research into what matters to people with COPD, in terms of managing their condition and supporting their wellbeing. We used a co-production methodology not previously applied in COPD, Working Together for Change (WTfC), to undertake a service evaluation. We aimed to identify what is important to people with COPD and what services would address these issues. Evaluation of the process has been described. 1 Here we report the themes that emerged from WTfC that reflect what mattered to participants. Methods: WTfC began with 45 structured one-to-one discussions between an evaluator and participants identified from a GP list. We asked three questions: "What is working well in terms of your COPD care?", "What is not working well in terms of your COPD care?" and "What is important to you?" Responses were analysed using quality improvement methods in two co-production workshops involving COPD patients and carers (including some of the one-to-one participants), local health care professionals and voluntary sector organisations. Responses were themed by all participants working together with an expert facilitator. The group agreed a label for each theme and participants voted on the most important themes under the heading "What's not working." Results: The themes in each category are presented in Table 1 . The six most important themes for "What's not working" were: "I don't think the right hand knows what the left hand is doing", "I can't get appointments when I want them", "I'm not treated as a person", "I can't do what I want to do", "I'm anxious and depressed" and "I can't eat well". Conclusions: What mattered to people with COPD encompassed not just health-related issues but also meaning, purpose and relationships. This underlines the importance of a patient-centred and holistic approach to delivering healthcare. This co-production process provided a non-clinical setting in which the patient voice could be heard and provide a meaningful input for health service planning. Reference: Early F, Winders S-J, Reddy SM, Ralphs JE, Fuld JP. Co-production to inform clinical commissioning in COPD: An evaluation of working together for change. Eur J Pers Cent Healthc 2017;5(1):111–119.